Buformin suppresses proliferation and invasion via AMPK/S6 pathway in cervical cancer and synergizes with paclitaxel. Issue 6 (3rd June 2018) - Li, Jing; Chen, Ling; Liu, Qiuli; Tang, Mei; Wang, Yuan; Yu, Jinjin
ABSTRACT: Buformin is an old anti-diabetic agent and manifests potent anti-tumor activities in several malignancies. In the present study, we aimed to explore the functions of buformin in human cervical cancer. As our data shown, buformin exhibited significant anti-proliferative effects in a dose-dependent manner in 4 cervical cancer cell lines. Compared to the control, buformin notably suppressed colony formation and increased ROS production in C33A, Hcc94 and SiHa cells. Flow cytometric analysis showed that buformin induced marked cell cycle arrest but only resulted in mild apoptosis. The invasion of C33A and SiHa cells sharply declined with buformin treatment. Consistently, western blotting showed that buformin activated AMPK and suppressed S6, cyclin D1, CDK4, and MMP9. Moreover, we found that buformin enhanced glucose uptake and LDH activity, increased lactate level, while decreased ATP production in cervical cancer cells. In addition, low doses of buformin synergized with routine chemotherapeutic drugs (such as paclitaxel, cisplatin, and 5-FU) to achieve more significant anti-tumor effects. In vivo, a single use of buformin exerted moderate anti-tumor effects, and the combination with buformin and paclitaxel exhibited even greater suppressive effects. Buformin also consistently showed synergistic effects with paclitaxel in treating primary cultures of cervical cancer cells. Take together, we are the first to demonstrate that buformin suppresses cellular proliferation and invasion through the AMPK/S6 signaling pathway, which arrests cell cycle and inhibits cellular invasion. Buformin also could synergize with routine chemotherapies, producing much more powerful anti-tumor effects. With these findings, we strongly support buformin as a potent choice for treating cervical cancer, especially in combination with routine chemotherapy.